1997
DOI: 10.1017/s0043174500092948
|View full text |Cite
|
Sign up to set email alerts
|

Implications of weed seedbank dynamics to weed management

Abstract: The species composition and density of weed seed in the soil vary greatly and are closely linked to the cropping history of the land. Altering tillage practices changes weed seed depth in the soil, which plays a role in weed species shifts and affects efficacy of control practices. Crop rotation and weed control practices also affect the weed seedbank. Information on the influence of cropping practices on the weed seedbank should be a useful tool for integrated weed management. Decision aid models use informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
180
0
15

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(202 citation statements)
references
References 65 publications
(66 reference statements)
7
180
0
15
Order By: Relevance
“…However, there are studies that show persistent weed problems in NT compared to CT even after several years (Anderson et al, 1998;Menalled et al, 2001), re-emphasizing that other management factors are important as well. Nonetheless, if carefully managed, the germination and emergence of a high proportion of the weed seed bank during the first year of NT can be used as an opportunity for long-term weed control (Egley and Williams, 1990;Buhler et al, 1997).…”
Section: Effect Of Tillage Practice On the Growth And Establishment Omentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are studies that show persistent weed problems in NT compared to CT even after several years (Anderson et al, 1998;Menalled et al, 2001), re-emphasizing that other management factors are important as well. Nonetheless, if carefully managed, the germination and emergence of a high proportion of the weed seed bank during the first year of NT can be used as an opportunity for long-term weed control (Egley and Williams, 1990;Buhler et al, 1997).…”
Section: Effect Of Tillage Practice On the Growth And Establishment Omentioning
confidence: 99%
“…Field traffic and machinery operations such as tillage provide opportunities to introduce or spread weed seeds (Schippers et al, 1993;Buhler et al, 1997). One study showed cultivation following harvest significantly increased weed seed dispersal (Heijting et al, 2009), and another found the weed seeds travelled 2-3 m in the direction of tillage, while in un-tilled soils the distance was negligible (Barroso et al, 2006).…”
Section: Effect Of Tillage Practice On Production Dispersal and Recmentioning
confidence: 99%
“…We hypothesize that knowledge of management practices over several years will improve the explanatory power of plant presence/absence models. Indeed, plant species such as weeds may exhibit long-lived seedbanks and unfavorable environmental conditions one year would not impede their emergence the following year (Buhler et al, 1997). A recent study has demonstrated that weed richness and biomass can successfully be predicted by the crop rotation of focal fields (Bohan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many agronomic aspects of land management influence the composition, density and diversity of a community of weeds (Buhler et al, 1997), particularly fertilization (Yin et al, 2005), tillage practices (Mulugeta and Stoltenberg, 1997), allelopathic interference and application of different herbicides (Haas and Streibig, 1982;Derksen et al, 1995;Chamanabad et al, 2009). Fertilization alters soil fertility, which affects not only crop growth, but also diversity and growth of associated weeds (Jornsgard et al, 1996;O'Donovan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%